2011
DOI: 10.1063/1.3546034
|View full text |Cite
|
Sign up to set email alerts
|

A synchrotron-based photoemission study of the MoO3/Co interface

Abstract: The electronic structures at the MoO(3)∕Co interface were investigated using synchrotron-based ultraviolet and x-ray photoelectron spectroscopy. It was found that interfacial chemical reactions lead to the reduction of Mo oxidation states and the formation of Co-O bonds. These interfacial chemical reactions also induce a large interface dipole, which significantly increases the work function of the cobalt substrate. In addition, two interface states located at 1.0 and 2.0 eV below the Fermi level are identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In Figure a, the work function of pristine VSe 2 is 4.70 eV, but we found that it varies from 4.70 to 5.10 eV depending on the coverage of VSe 2 on HOPG (see Figure S1). Upon deposition of MoO 3 , the work function gradually increases and reaches 6.43 eV at 14 Å MoO 3 thickness, close to the reported saturation work function (∼6.50–6.86 eV) of MoO 3 , indicating a complete coverage by MoO 3 , consistent with our STM data. A close inspection of the SECO spectra for 0.5, 1, and 2 Å MoO 3 thicknesses reveals two sets of cutoff edges, which arise from the nonuniform coverage of MoO 3 as a result of the island growth mode.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In Figure a, the work function of pristine VSe 2 is 4.70 eV, but we found that it varies from 4.70 to 5.10 eV depending on the coverage of VSe 2 on HOPG (see Figure S1). Upon deposition of MoO 3 , the work function gradually increases and reaches 6.43 eV at 14 Å MoO 3 thickness, close to the reported saturation work function (∼6.50–6.86 eV) of MoO 3 , indicating a complete coverage by MoO 3 , consistent with our STM data. A close inspection of the SECO spectra for 0.5, 1, and 2 Å MoO 3 thicknesses reveals two sets of cutoff edges, which arise from the nonuniform coverage of MoO 3 as a result of the island growth mode.…”
Section: Resultssupporting
confidence: 90%
“…In other words, monolayer VSe 2 behaves like a noble metal. The band alignment at the MoO 3 –VSe 2 interface is proposed in Figure , in which we take the work function of MoO 3 as 6.6 eV according to the literature, whereas the work function of monolayer VSe 2 is 5.1 eV, the largest experimental value obtained in this work. Without loss of generality, the band gap of MoO 3 is assumed to be 3.0 eV (averaged from the reported values ,, ), and the energy difference between the VB maximum (VBM) and Fermi level is 2.5 eV, as determined from Figure .…”
Section: Resultsmentioning
confidence: 95%
“…A number of studies have demonstrated chemical interactions between oxides and metal electrodeswithin the first few nanometers of an interface-and also dependence of device performance on the electrode material. 66,70,[218][219][220][221][222] Chemically reactive interfaces can give rise to reduction of oxidation state in the oxide buffer layer near the electrode/buffer interface. For instance, MoO 3 on metals with various reactivity gives rise to reduced MoO 3 near the metal/metal-oxide interface, as illustrated in Figure 13.…”
Section: Opportunities and Challenges Of Metal Oxides As Ultrathin Bumentioning
confidence: 99%
“…A 3.5 Å thick Co oxide layer was found also in the interfacial region of ultra-thin chromia films grown on the Co(0001) surface [182]. Wang et al studied the MoO 3 /Co layered system, finding a reduction of the oxidation state of Mo in the interfacial region, along with the formation of Co oxide [183].…”
Section: Late 3d Transition Metals Substratesmentioning
confidence: 99%